PERFORMANCE EFFICIENCY OF THE ADVENTIST BOOK CENTERS IN INDONESIA: A DATA ENVELOPMENT ANALYSIS - Lule, Benny (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
This paper aims to analyze the performance efficiency of the Adventist Book Centers (ABCs) in Indonesia. This paper uses DEA approach to analyze twelve (12) ABCs over the period 1993 – 2003. The findings shows that the ABCs have a TFP index mean of 1.027, which is decomposed to EFFCH index mean of 0.989 and TECHCH index mean of 1.038. It also shows that 7 of 12 are productive ones. Additionally, the finding shows that the ABCs have negative growth of efficiency. They have EFFCH mean index of 0.989 which is decomposed into PECH and SECH that have index scores of 0.992 and 0.997, respectively.